Increased nociceptive sensitivity and nociceptin/orphanin FQ levels in a rat model of PTSD - Zhang Yong; Gandhi Priyam R; Standifer Kelly M (Molecular Pain, 2012)
Abstract Background Clinical studies indicate that post-traumatic stress disorder (PTSD) frequently shares co-morbidity with chronic pain. Although in animals acute stress-induced antinociception is well documented, the effect of PTSD-like stress on nociceptive sensitivity is unclear. Though a few studies measured nociceptive responses at a single time point, no studies have examined changes in nociceptive sensitivity over time following exposure to PTSD-like stress. Nociceptin/orphanin FQ (N/OFQ), an endogenous ligand for the N/OFQ peptide (NOP) receptor, modulates various biological functions in the central nervous system that are affected by PTSD, including nociceptive sensitivity, stress and anxiety, learning and memory. Results The present study examined thermal and mechanical nociceptive sensitivity in male Sprague Dawley rats between 7 and 28 days after single-prolonged stress (SPS), an established animal model for PTSD. Rat paw withdrawal thresholds (PWT) to von Frey and paw withdrawal latencies (PWL) to radiant heat stimuli, respectively, dramatically decreased as early as 7 days after initiation of SPS and lasted the length of the study, 28 days. In addition, N/OFQ levels increased in cerebrospinal fluid (CSF; on days 9, 14 and 28) and serum (day 28), while levels of circulating corticosterone (CORT) decreased 28 days after initiation of SPS. SPS exposure induced anxiety-like behavior and enhanced inhibition of the hypothalamo-pituitary-adrenal (HPA) axis, as previously reported for this model. Conclusions Our results demonstrate that SPS induces the development of persistent mechanical allodynia and thermal hyperalgesia that is accompanied by increased N/OFQ content in the CSF, and eventually, in serum. These findings suggest a link between N/OFQ and the development of hyperalgesia and allodynia in a rat model of PTSD.